Penerapan Rendam Kaki Air Hangat Pada Lansia Dengan Hipertensi Di Desa Susukan - Aska Niswa; Tri Susilowati (STIKes Ibnu Sina Ajibarang, 2023)
Background: Age 60 years and over is the final stage of the aging process which has a biological impact, one of which is susceptibility to disease, for example hypertension, which is a chronic increase in blood pressure of more than 140/90 mmHg. Cases of elderly people with hypertension in Susukan Village, according to the elderly posyandu cadres, were 53 people. Hypertension can be treated pharmacologically by using drugs and non-pharmacologically by therapy with warm water foot soaks. Purpose: Knowing the difference in blood pressure before and after soaking feet in warm water. Methods: This case study is intended to obtain the results of applying warm water foot soaks to elderly people with hypertension with two elderly people living in Susukan Village, Semarang Regency as subjects. Results: After soaking the feet, it was found that the average decrease in systolic blood pressure in Mrs. H 6 mm Hg and Mrs. N 5 mmHg while the average diastolic blood pressure in Mrs. H 5 mm Hg and on Mrs. N 4 mmHg every day. Conclusion: Researchers concluded that there was a decrease in blood pressure after a 5-day study as indicated by a decrease in systolic pressure in Mrs. H 28 mm Hg and Mrs. N 24 mmHg while there was a decrease in diastolic in Ny. H 23 mmHg and Mrs. N 18 mmHg.